Ownership, Board Compensation and Company Performance in Sub-Saharan African Countries - Gibson Hosea Munisi; Roy Mersland (Journal of Emerging Market Finance, 2016)
In countries with weak institutions, board governance becomes more important. This study uses a unique dataset from listed sub-Saharan African companies to examine the relationship between ownership composition and board compensation. It further analyses the association between board compensation and company performance. The findings indicate that board ownership and chief executive officer ownership are positively associated, whereas state ownership and concentrated ownership are negatively associated with board compensation. There is no evidence of a significant association between chairperson ownership or foreign ownership and board compensation. Finally, there is a negative but not significant relationship between board compensation and company performance.
Keywords: G32; G34; 330